PENGARUH PERSEPSI KARYAWAN MENGENAI WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD DENGAN PERILAKU ETIS SEBAGAI VARIABEL INTERVENING - Alfian, Nurul; Sugiyardi, Agus; Aina, Muslimatul; Kusuma, Andriyani; Fajar, Achmarul; Rizal, Zef (Fakultas Ekonomi, Program Studi Akuntansi, 2021)
This study aims to determine: (1) Effect of Employee Perception Regarding Whistleblowing System on Fraud Prevention, (2) Effect of Employee Perception Regarding Whistleblowing System on Ethical Behavior, (3) Effect of Ethical Behavior on Fraud Prevention, (4) Effect of Employee Perception Regarding Whistleblowing System for Fraud Prevention through Ethical Behavior. This research is a type of comparative causal research. The population of this research is all employees who work. Sampling was done by using purposive sampling technique. The sample in this study were all employees of the Office of the Board of Directors of PT Pagilaran. Before the research was conducted, the instrument was tested first involving 30 employees. The analytical prerequisite test tools used in this research are normality test, linearity test and heteroscedasticity test. The data analysis method used to test the research hypothesis is path analysis and Sobel Test. The results of the hypothesis test show: (1) Employee Perception Regarding Whistleblowing System has a significant positive effect on Fraud Prevention, this is evidenced by the significance probability value of 0.004 (< t table (2.042).